Structural, magnetic, thermal and thermoelectrical properties of mononuclear and dimeric cobalt(II) and iron(II) complexes with extended π-conjugated bipyridyl ligands / Nik Muhd Jazli Nik Ibrahim - Nik Muhd Jazli, Nik Ibrahim (2016)
This research was focused on syntheses and characterisation of Co(II) and Fe(II) complexes with four π-conjugated bipyridyl ligands (L), designed to be thermally stable and have magnetic and thermoelectric properties. A total of 16 complexes were successfully synthesized and characterised. Their general formulae were [M2(CH3COO)4(L)2] and[M(L)3](BF4)2 where M = Co(II) and Fe(II). The structures of L were ascertained by CHN elemental analyses, 1H-NMR and FTIR spectroscopies, while the structures of all complexes were deduced from CHN elemental analyses and FTIR and UV-vis spectroscopies. The magnetic properties of complexes were determined at room temperature by the Gouy method, their band gaps were determined by UV-vis spectroscopy and cyclic voltammetry (CV), their thermal stability by thermogravimetry (TG) and their thermoelectrical properties deduced from their Seebeck coefficients, Se. At room temperature, most of these complexes have both high spin and low spin Co(II) and Fe(II) atoms. Their decomposition temperatures were in the range of 170 oC – 265 oC, optical bandgaps in the range of 1.85 eV – 2.75 eV, and electrochemical bandgaps in the range of 0.32 eV – 0.55 eV. Their electrochemical bandgaps were beneficial for good thermoelectrical performance, as supported by relatively high Seebeck coefficients (-0.35 ± 0.02 mV K-1 – -0.62 ± 0.02 mV K-1).